2011
DOI: 10.1007/s11064-011-0578-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Recurrent Neonatal Seizures on Neurobehavioral Function and Related Gene Expression and Its Intervention by Inhibitor of Cathepsin B

Abstract: Cathepsins are families of proteases that have been reported to play the key roles in neuroexcitotoxicity. The present study was sought to determine the effect of CBI, a cathepsin B inhibitor, in the prevention of neurobehavioral deficits after inhalant flurothyl-induced recurrent neonatal seizures in rats. We examined the expression pattern of autophagy-related genes at acute phase after the last seizures using western blot method, and evaluated behavioral deficits during postnatal day 28 (P28) to P35. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Thus, establishing the molecular pathways associated with the seizure-induced neuronal death may provide novel treatment strategies for patients with TLE. Although enhanced levels/expression of lysosomal enzymes does not always correlate with the degeneration of neurons, there is evidence that administration of kainic acid can lead to up-regulation of lysosomal enzymes in the affected regions of the brain (Hetman et al, 1995;Tominaga et al, 1998;Akahoshi et al, 2007;Ni et al, 2012). This finding is substantiated, in part, by our study which shows an increase in the expression, levels and activity of cathepsins B and D in the hippocampus of kainic acid-treated rats compared to controls.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Thus, establishing the molecular pathways associated with the seizure-induced neuronal death may provide novel treatment strategies for patients with TLE. Although enhanced levels/expression of lysosomal enzymes does not always correlate with the degeneration of neurons, there is evidence that administration of kainic acid can lead to up-regulation of lysosomal enzymes in the affected regions of the brain (Hetman et al, 1995;Tominaga et al, 1998;Akahoshi et al, 2007;Ni et al, 2012). This finding is substantiated, in part, by our study which shows an increase in the expression, levels and activity of cathepsins B and D in the hippocampus of kainic acid-treated rats compared to controls.…”
Section: Discussionsupporting
confidence: 62%
“…These results suggest that cathepsins may have a role not only in normal cellular functioning but also in a variety of disorders associated with the degeneration of neurons, including TLE. Although some earlier studies have reported altered levels and/or activity of cathepsins in kainic acidinduced seizures (Hetman et al, 1995;Tominaga et al, 1998;Akahoshi et al, 2007;Ni et al, 2012), very little is known about the subcellular levels of the enzymes and their association, if any, to the degeneration of neurons. To address this issue, we measured the time-dependent alterations in the distribution, activity and cellular/subcellular levels of cathepsins B and D in the hippocampus of adult rats following systemic administration of kainic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Outcome varies depending on the ELS protocol. Multiple brief seizures induced by FL during the first post-natal weeks are consistently reported to result in spatial learning deficits later in life in the Morris water maze (MWM), typically with acquisition (learning) (Bo et al, 2004; Chang et al, 2003; de Rogalski Landrot et al, 2001; Holmes et al, 1998; Huang et al, 1999; Karnam et al, 2009a, b; Lugo et al, 2014b; Mikati et al, 2005; Neill et al, 1996; Ni et al, 2012). …”
Section: Behavioral Phenotypes Following Elsmentioning
confidence: 99%
“…A total of 48 Sprague-Dawley neonatal rats at postnatal day 6 (P6) were randomly divided into four groups: Control (Cont), melatonin-treated control (Mel), recurrent neonatal seizure (RS) and melatonin and RS combined treatment (Mel+RS). The procedure of seizure induction was described in detail previously (16). In brief, the neonatal rats were placed into a transparent plastic airtight box and liquid volatile flurothyl (bis-2,2,2-triflurothyl ether; Sigma-Aldrich, St. Louis, MO, USA) was added, using a syringe, onto filter paper in the center of the container, for agent evaporation.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study investigated the dynamic expression pattern of mossy fiber sprouting-associated genes in the rat brain using a flurothyl-induced recurrent neonatal seizure model. Furthermore, this model, as described extensively, has been widely used to evaluate the neuroprotective efficacy of compounds, including autophagy inhibitor 3-MA, CBI and E-64d (14)(15)(16). The important function of melatonin in epilepsy, and the requirement to elucidate its role in neonatal seizure-induced long-term excitotoxicity, prompted the present study to further examine whether pretreatment with melatonin alleviates the deleterious changes in the hippocampus.…”
Section: Long-term Expression Of Metabolism-associated Genes In the Rmentioning
confidence: 99%